Fertility, gestation outcome and parasite congenital transmissibility in mice infected with TcI, TcII and TcVI genotypes of Trypanosoma cruzi. - Sabrina Cencig; Nicolas Coltel; Carine Truyens; Yves Carlier (PLoS Neglected Tropical Diseases, 2013)
This work aims to compare the effects of acute or chronic infections with the T. cruzi genotypes TcI (X10 strain), TcII (Y strain) and TcVI (Tulahuen strain) on fertility, gestation, pup growth and the possible vertical transmission of parasites in BALB/c mice. The occurrence of congenital infection was evaluated by microscopic examination of blood and/or qPCR on blood and heart in newborn pups and/or older offspring submitted to cyclophosphamide-induced immunosuppression in order to detect possible cryptic congenital infection. Altogether, the results show that: i) for the three strains tested, acute infection occurring after the embryo implantation in the uterus (parasite inoculation 4 days before mating), or close to delivery (parasite inoculation on day 13 of gestation), prevents or severely jeopardizes gestation outcome (inducing pup mortality and intra-uterine growth retardation); ii) for the three strains tested, gestation during chronic infection results in intra-uterine growth retardation, whereas re-inoculation of TcVI parasites during gestation in such chronically infected mice, in addition, strongly increases pup mortality; iii) congenital infection remains a rare consequence of infection (occurring in approximately 4% of living pups born to acutely infected dams); iv) PCR, detecting parasitic DNA and not living parasites, is not convenient to detect congenial infection close to delivery; v) transmission of parasites by breast milk is unlikely. This study should encourage further investigations using other parasite strains and genotypes to explore the role of virulence and other factors, as well as the mechanisms of such effects on gestation and on the establishment of congenital infection.